Is Your Color My Color? Dividing the Labor of the Stroop Task Between Co-actors - Yamaguchi, Motonori; Clarke, Emma L.; Egan, Danny L. (Frontiers in Psychology, 2018)
Performing a task with other actors involves two opposing forces, division of labor between co-acting individuals and integration of divided parts of the task into a shared mental representation (co-representation). Previous studies have focused primarily on the integration of task representations and limited attention has paid to the division of labor. The present study devised a new test of the integration and the division in a joint task setting. A joint version of the Stroop task was developed, in which pairs of actors were assigned different sets of target colors. If the actors integrate their co-actor’s task, the colors assigned to their co-actor should be represented as if they were the actor’s own target colors; the Stroop effect should be as large when distractor color words denote their co-actor’s target colors as when these words denote the actor’s own target colors. If the actors divide the labor of the Stroop task, the colors assigned to their partner should be represented as non-target colors; the Stroop effect should be smaller when the distractor color words denote the co-actor’s target colors than when these words denote the actor’s own target colors. The results of response time did not provide clear support for either position, while those of response accuracy supported the division of labor. Possible cognitive mechanisms that support the division of labor and the integration of task representation are discussed.